AIDS denialism: Arguments and epistemological discussion - Moquillaza-Alcantara, Victor Hugo (2024)
Objective: To identify and confront the denialist arguments with historical epistemological concepts. Material and methods: A review was conducted in Pubmed and Scopus to identify scientific arguments that deny AIDS, using terms related to “denial”, “AIDS” and “HIV”. Observational studies, notes, essays, and letters to the editor were included, and the selected arguments were analyzed based on epistemological positions to explain their errors. Results: The search revealed few manuscripts in the scientific literature that deny the existence of HIV or AIDS. These arguments fall into four categories: 1) low HIV deaths compared to positive cases, 2) population increase despite AIDS, 3) toxicity of antiretrovirals outweighing their benefits, and 4) origin of AIDS in drugs, antiretrovirals and malnutrition. Conclusion: None of the AIDS denialist arguments has a valid epistemological foundation and their origin is found in political contexts that defend pseudoscientific positions. AIDS deniers have not conducted research to verify their hypotheses, relying on criticism and erroneous interpretations. History shows that it is the responsibility of scientists to curb pseudoscience and provide correct and accessible interpretations to society.